The Relationship Between Sedentary Lifestyle and the Risk of Type 2 Diabetes Mellitus in Generation Z - Nurdina Nurdina; Kurnia Harli; Irfan Wabula (Lembaga Penerbitan Fakultas Kesehatan, Universitas Kristen Indonesia Maluku, 2025)
Approximately 90% of diabetes cases in Indonesia are classified as type 2 diabetes mellitus (T2DM). In Indonesia, particularly among Generation Z, sedentary lifestyles are becoming increasingly prevalent. The primary aim of this study was to examine the association between sedentary lifestyle and the risk of type 2 diabetes mellitus among Generation Z. A cross-sectional design was employed, with 135 respondents selected through purposive sampling. The study participants were undergraduate students from the 2023 cohort of the Accounting Study Program, Faculty of Economics, University of West Sulawesi. Data were collected using the Adolescent Sedentary Activity Questionnaire (ASAQ) and the Finnish Diabetes Risk Score (FINDRISC). The findings revealed that 101 respondents (74.8%) demonstrated a high sedentary lifestyle, while 5 respondents (3.7%) exhibited a high risk of developing type 2 diabetes mellitus. Results from the Chi-square test indicated a p-value of 0.861, which is greater than ? = 0.05, suggesting that there is no significant relationship between sedentary lifestyle and the risk of type 2 diabetes mellitus in Generation Z. In conclusion, this study found no significant association between sedentary lifestyle and the risk of type 2 diabetes mellitus among Generation Z.